Difficulties of diagnostics of epilepsy due to molybdenum cofactor deficiency: a case report - A. G. Malov; Yu. V. Karakulova; M. Severino; Yu. I. Kravtsov (Русский журнал детской неврологии, 2019)
The article presents a clinical study of an infant with rare inherited metabolism disorder – molybdenum cofactor deficiency, for the first time in Russian literature. The onset of disorder – in early neonatal period with a suppression syndrome and myoclonic seizures combined with a burstsuppression electroencephalographic patterns, followed by a reveal of psychomotor delay. Сraniofacial dystrophies were present, including craniostenosis and microcephaly. Somatic status was characterized by hepatolienomegaly, dysmetabolic changes of kidneys’ parenchyma (suggested by ultrasound) and crystalluria. Neuroimaging data were contradictory. Neurosonography results allowed diagnosing concomitant inborn brain development defect: true porencephalia of large hemispheres. However, brain magnetic resonance imaging revealed a picture of diffuse leukomalacia with pseudocyst formation, which were considered a consequence of perinatal brain damage. Magnetic resonance imaging revealed a picture of diffuse leukomalacia with pseudocyst formation, which were considered a consequence of perinatal brain damage. Differential diagnosis was held between the early infantile epileptic encephalopathy (Ohtahara syndrome) and early myoclonic encephalopathy (Aicardi syndrome). However, etiology of the disease remained unclear. To eliminate inherited metabolic disease accompanied by epilepsy, Inherited Epilepsy Panel DNA sequencing was used. The results showed a homozygotic mutation on the exon 6 of MOCS2 gene, leading to deletion of amino acid in position 158 of the protein, which was described before in patients with molybdenum cofactor deficiency (OMIM: 252160).